Needs Analysis of STEM-PBL E-Modules Integrating Papuan Local Wisdom to Support Critical Thinking and Creativity in Sound Wave Learning - Aminnudin, Ergianto; Suharno; Sukarmin (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2026)
Physics learning in secondary schools still faces obstacles in developing students' critical thinking skills and creativity, especially due to the limitations of digital teaching materials that are contextual and integrated with local wisdom. This study aims to analyze the needs, implementation constraints, and perceptions of physics teachers towards the development of STEM-PBL e-modules based on Papuan local wisdom on sound wave materials. This study is a needs analysis study at the Analyze stage in the ADDIE model with a mixed method approach through a descriptive survey. The subjects of the study were 11 high school physics teachers in Merauke Regency who were selected purposively. Data were collected through Likert scale questionnaires and interviews, then analyzed quantitatively-descriptively and qualitative-thematic. The results of the study showed that as many as 81.82% of teachers were interested in developing modules containing local wisdom, 84.09% had used experimental methods, and 75.00% had implemented PBL. However, there is a gap between interest and implementation capacity, where 63.64% of teachers have difficulty developing modules with local wisdom, only 52.27% apply STEM-PBL in an integrated manner, and the integration of local wisdom is still partial even though 93.18% of teachers consider sound wave material as an essential topic. Based on the teacher's perspective, the need for STEM-PBL e-modules based on Papuan local wisdom arises from the gap between the learning practices that have taken place and the demands of integrated contextual learning implementation. These findings show the need to develop e-modules that provide systematic STEM-PBL integration, relevant Papuan cultural contexts, and pedagogical guidance that can support teachers in implementing sound wave learning in a more structured and meaningful way.